Dexamethasone-Induced FKBP51 Expression in CD4+ T-Lymphocytes Is Uniquely Associated With Worse Asthma Control in Obese Children With Asthma - Tejwani, Vickram; McCormack, Amanda; Suresh, Karthik; Woo, Han; Xu, Ningchun; Davis, Meghan F.; Brigham, Emily; Hansel, Nadia N.; McCormack, Meredith C.; D’Alessio, Franco R. (Frontiers in Immunology, 2021)
Introduction: There is evidence that obesity, a risk factor for asthma severity and morbidity, has a unique asthma phenotype which is less atopic and less responsive to inhaled corticosteroids (ICS). Peripheral blood mononuclear cells (PBMC) are important to the immunologic pathways of obese asthma and steroid resistance. However, the cellular source associated with steroid resistance has remained elusive. We compared the lymphocyte landscape among obese children with asthma to matched normal weight children with asthma and assessed relationship to asthma control. Methods: High-dimensional flow cytometry of PBMC at baseline and after dexamethasone stimulation was performed to characterize lymphocyte subpopulations, T-lymphocyte polarization, proliferation (Ki-67+) and expression of the steroid-responsive protein FK506 binding protein 51 (FKBP51). T-lymphocyte populations were compared between obese and normal-weight participants, and an unbiased, unsupervised clustering analysis was performed. Differentially expressed clusters were compared to asthma control, adjusted for ICS and exhaled nitric oxide. Results: In the obese population, there was an increased cluster of CD4+ T-lymphocytes expressing Ki-67 and FKBP51 at baseline and CD4+ T-lymphocytes expressing FKBP51 after dexamethasone stimulation. CD4+ Ki-67 and FKBP51 expression at baseline showed no association with asthma control. Dexamethasone-induced CD4+ FKBP51 expression was associated with worse asthma control in obese participants with asthma. FKBP51 expression in CD8+ T cells and CD19+ B cells did not differ among groups, nor did polarization profiles for Th1, Th2, Th9 or Th17 percentages. Discussion: Dexamethasone-induced CD4+ FKBP51 expression is uniquely associated with worse asthma control in obese children with asthma and may underlie the corticosteroid resistance observed in this population.